The Effectiveness of A Training Program Using Vertical Jump Device (Vertimax) on Some Biomechanical Variables in Performance of Undulating Serve Skill in Volleyball for Players - Aqeel Yousif Naser (Program Studi Pendidikan Kepelatihan Olahraga, 2026)
Development of biomechanical elements associated with performance and precision of some fundamental volleyball skills is where research is most important using exercises on training device (vertimax), which considers demands of particular talent when training on it, as training is carried out according to motor paths of each skill independently to advance physical elements of trained skills, which are reflected in biomechanical aspects of each skill, which differs from traditional methods of giving physical exercises, as physical and skill training on this device is closer to nature of players' talent performance on field. In addition, exercises have been built on a mechanical basis that matches character of skill's real on-field performance. research's objectives are to design exercises with Verti Max device that are appropriate for research sample's abilities and to determine how these exercises affect development of certain biomechanical markers of young volleyball players' proficiency with undulating serve from jump. research community consists of young volleyball players from Babylon clubs (Al-Mahaweel Club) youth category, numbering (16) players. following criteria were used to choose research sample: They will be Al-Mahaweel Sports Club's young players for 2022–2023 season, and there will be ten of them. players were split up into two groups by researcher: a control group and an experimental group, which was assigned a number of five, numbering (5), and they constitute (63%) of total community. This was done by drawing lots, as investigator came to conclusion that suggested workouts have an effect in developing skill of crushing in some biomechanical variables (angular velocity of striking arm, shoulder angle now of striking, instantaneous velocity of ball’s exit, and torso angle at moment of striking).